Rare autoantibodies to cellular antigens in systemic lupus erythematosus. (June 2014) - Fredi, M; Cavazzana, I; Quinzanini, M; Taraborelli, M; Cartella, S; Tincani, A; Franceschini, F
Objective: A high number of antinuclear antibody specificities can be detected in systemic lupus erythematosus (SLE). Some of them are related to a distinct clinical subset of disease, independently of their frequency. The aim of our study was to investigate, in a cohort of SLE patients, the prevalence and the clinical relevance of autoantibodies to cellular antigens less frequently found in SLE. Methods: Antinuclear antibodies were detected by indirect immunofluorescence on HEp-2 cells while counterimmunoelectrophoresis was used to detect anti-ENA antibodies in 540 patients with SLE, classified according to ACR and SLICC criteria. Clinical and serological features were collected from clinical charts. Results: A total of 319 (58.9%) out of 540 sera were positive for anti-ENA antibodies. Anti-Ro/SSA was found in 235 sera, 50 of which also contained anti-La/SSB. Anti-U1RNP were detected in 67, anti-Sm in 46 and anti-ribosomal P protein in 13 sera. In a multivariate analysis anti-Sm was associated with discoid lupus ( p = 0.045) and photosensitivity ( p = 0.037), anti-U1RNP with malar rash and Raynaud's phenomenon ( p = 0.01 and p = 0.0004, respectively) and anti-Ro/SSA with malar rash, oral ulcers, xerostomia, xerophthalmia and rheumatoid factor ( p = 0.029, p = 0.01, p = 0.031, p = 0.002 and p = 0.028, respectively). Other anti-ENA antibodies were found in 50 positive sera (15.6%). Anti-Ki antibodies were detected in 31, anti-Ku in 8, anti-centromere in 5, isolated anti-La/SSB, anti-PCNA and anti-Topo I in 3 each and anti-Jo-1 in 2 sera. About half of these antibodies (27 out of 50) were detected as the single anti-ENA specificity in serum. At multivariate analysis anti-Ki was significantly associated with male gender while anti-Ku with African ethnicity ( p = 0.017 and p < 0.0001, respectively). No sign of muscular or pulmonary involvement was found in anti-Jo-1-positive patients whilst features of systemic sclerosis were detectable in two out of three anti-Topo I. Conclusions: Our study shows that antibodies to cellular antigens more rarely found in SLE are detectable in more than 15% of patients with anti-ENA antibodies. Most of them are found as single anti-ENA specificity. Anti-Ki and anti-Ku are found in a subset of disease, characterized by male gender and African origin, respectively. Clinical features of scleroderma were found only in patients with anti-Topo I.